(untitled) (Archive of Conferences, 2022)
at any stage of human civilization, the age-old struggle between good and evil, light and darkness, ignorance and enlightenment will continue. On the pages of our history, too, live the immortal names of people who, having sewed their lives, their lives, to overcome ignorance. One of such writers, Abdulla Avlani’s efforts to create the light of enlightenment, zalvorli, will be analyzed in detail in the following article.